Investigating the Digital Parenting Behaviors of Parents on Children's Digital Game Play - Fidan, Ayca; Gunes, Habibe; Karakus Yilmaz, Turkan (Cukurova Univ, 2021)
This article aims to understand the attitudes, mediating and monitoring behaviors of parents related to the digital games played by their children. For this qualitative research, 30 parents answered 14 open-ended questions. Data analyzed descriptively. The data were analyzed with respect to the research questions and the analysis showed that the findings could be grouped into three themes: attitudes, monitoring, and mediating. The findings of the study demonstrated that parents thought that educational games developed their children mentally, developed their critical thinking skills, enabled them to follow up on how to benefit of those games, and developed their imagination. The research findings revealed that parents limited the time that their children spent with digital games; tried to be careful with regard to their children's choices of digital games; and had positive attitudes toward educational games, but not others. The results implicated that parents need to raise their digital parenting approach. It should be noted that digital parenting does not mean parents to play more digital games. Instead of that it provides them to teach their children the risks and gains that may face in digital games.
Keywords: Digital Parenting; Parental Mediation; Digital Games; Parent-Child Relationship; Qualitative Research